Introducing a Client-Centred Focus into the Law School Curriculum - Robin Handley; Damien Considine (Legal Education Review)
This paper examines recent research showing widespread dissatisfaction with the legal profession, especially as a result of failures in lawyer/client communications. We ask whether part, at least, of the blame lies with law schools, who largely neglect the client in the law degree curriculum. The question then posed is, what is the role of our law schools and to what extent should clients be a part of their perspective, particularly at a time when the nature of legal practice is undergoing profound change. One indication of this is the emphasis or lack of emphasis given to teaching skills in the law degree curriculum, especially those skills which give context to the law and affect the consumer of legal services, the client. We consider the relationship between the law degree and practical legal training courses, what skills are currently taught by law schools, and ask what skills might be included in the law degree curriculum and with what effect. We conclude that a client-centred approach to legal education — one which includes the client in the law school curriculum — could make a significant contribution to redressing failures in lawyer/client communication and also make the law degree a more focused and interesting course of study.